Processing of materials at cryogenic temperature and its implications in manufacturing: A review. Issue 15 (18th November 2018) - Singla, Anil Kumar; Singh, Jagtar; Sharma, Vishal S.
ABSTRACT: Processing of materials at cryogenic temperature has improved the properties of materials such as hardness, toughness, wear resistance, tensile strength, dimensional stability, corrosion resistance, etc. However, the extent of improvement in the properties of materials subjected to cryogenic treatment as claimed in the literature is diverse and sometimes contradictory to each other. Contradictions have also been reported regarding its various aspects like tempering prior and postcryogenic treatment, tempering temperature, aging before cryogenic treatment and cryogenic parameters like soaking temperature, soaking time, and cooling rate. There is need of investigating the cryogenic treatment in relation to pre and postheat treatment conditions. In this study, an attempt has been made to review the various research articles published in the literature on the subject matter extensively. Cryogenic processing of cutting tools and workpiece material has also emerged as a potential technique for improving the performance of cutting tools during metal cutting as well as for improving the machinability and weldability of workpiece materials. The implications of cryogenic treatment in the perspective of manufacturing have been revealed clearly through review of related studies. The various findings reported in the literature have been highlighted systematically and futuristic directions have been proposed to encourage research work in the area of cryogenic treatment.